Assessment of the relationship between urinary iodine level and thyroid dysfunction among children in South India- A case-control study - Vignesh Sivaraj; Subbarayan Sarojini; Arul Suyambunathan V; Suresh Pichandi; Desigamani Kanniyappan; Ramadevi Kanakasabapathi (Journal of Krishna Institute of Medical Sciences University)
Background: A universal salt iodization program was implemented in India to eradicate Iodine Deficiency Disorders (IDD) in children. Iodine deficiency is eliminated but excess iodine in children could lead to complications in the thyroid gland. Aim and Objectives: To assess urinary iodine levels and thyroid dysfunction among children. Material and Methods: One hundred children between the ages of 6 to 12 years with thyroid dysfunctions and 100 age- and gender-matched healthy children were enrolled in the case-control groups respectively. All subjects were measured for urinary iodine, thyroid profile, anti-microsomal antibody, and anti-thyroglobulin antibody levels. Goiter grading and Fine Needle Aspiration Cytology (FNAC) were performed. Results: Elevated levels of urinary iodine were found in 77% of the case population. Hypothyroidism (66%), hyperthyroidism (11%), and benign goiter (23%) thyroid complications were observed in the case group. FNAC and autoantibody reports confirmed 66% of autoimmune thyroiditis found in the case group. Conclusion: Higher levels of urinary iodine excretion suggest the consumption of excess iodine intake in children. An elevated level of autoantibodies with iodine excess may lead to thyroid complications such as thyroiditis, thyrotoxicosis, and benign goiter in children. So, a continuous supply of iodized salt should be monitored carefully.